(untitled) (Indonesian Journal of Technology and Computer Science, 2025)
The development of information and communication technology has brought significant changes to various service sectors, including the Event Organizer (EO) and Wedding Organizer (WO) industries. In today’s digital era, people demand ease, speed, and transparency in obtaining event management services. However, in regions such as Pontianak City, many EO and WO providers still use manual management systems, resulting in various challenges such as difficulties in managing customer data, coordinating with vendors, and generating administrative reports. This study aims to develop a web-based information system that can integrate all EO and WO business processes, ranging from customer management, event scheduling, vendor management, service booking, to activity reporting. The research method was conducted through a literature review of four journals related to EO and WO information systems, as well as system design using the Unified Modeling Language (UML) approach. The results indicate that the implementation of digital information systems can enhance operational efficiency, accelerate service delivery, and increase customer trust in service providers. This study is expected to serve as a solution for EO and WO practitioners in Pontianak to adapt to technological developments and improve competitiveness in the digital era.